Pengaruh Hambatan Samping Terhadap Kinerja Jalan Pada Sipang Bersinyal (Studi Kasus Jl. Abdullah Daeng Sirua dan Jl. Adyaksa Baru Kota Makassar) - Kadir, Hamdan; Akram, Andi Muhammad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
On the section at the signalized intersection of Jl. Abdullah Dg. Sirua – Jl. Adyaksa Baru Makassar City's traffic flow uses a two-way system, on this section of road the volume of vehicle traffic is quite dense plus there is high side obstacle activity because it is a trade business area such as offices, banking, shops, restaurants and shopping centers where transactions take place. sellers and buyers and there is a place of worship. Side barriers in the signalized intersection area on Jalan Abdullah Dg.Sirua – Jl. Adyaksa Baru in its existing condition obtained the highest value at point 1 on Monday at 16:30-17:30 WITA with an occurrence frequency of 456 Kej/hour per 200 m and a weight frequency of 298 Kej/hour. In this side resistance condition, it can be categorized as a low condition (Low)